The Role of Risk Management in Business Plan Preparation: A Case Study of Dessert Podsgirls.id - Nita Puspitasari (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
Risk management is an important part of creating an effective business plan, especially for new businesses such as “Dessert article is to analyze how risk management can be integrated into a business plan to identify and mitigate potential risks that can impact business success. This study uses a qualitative approach to examine the steps of risk identification, assessment, and mitigation carried out by “Dessert Podsgirls.id”. The findings show that “Dessert Podsgirls.id” can improve operational resilience and competitiveness in the market by implementing systematic risk management. In addition, integrating risk management into business planning allows managers to make more accurate and strategic decisions, thereby increasing investor confidence. Thus, risk management not only serves as a tool to avoid losses but also creates opportunities for sustainable growth. Keywords: Risk Management, Business Plan, Culinary